トウケイ 37 ド 45 ド カン エンガン イキ ノ チズ サクセイ ニツイテ - 吉田, 新生; ヨシダ, アラオ; 鈴木, 利男; スズキ, トシオ; YOSHIDA, Arao; SUZUKI, Toshio (国立極地研究所, 1964)
P(論文) By the time the sixth Japanese Antarctic Research Expedition came to an end, the features of coastal region, between 37° and 45° E in longitude, had been more and more clarified, with increasing air photographs and ground control points. Consequently, map compilation was planned in the early part of 1962. Then, the plotting for about 330 models on the basis of vertical photographs was carried out by photogrammetric experts in the Geographical Survey Institute, using Zeiss Stereotope. In addition, aerial triangulation for 162 models was carried out in the same period, using Wild Universal Autograph A7 and Zeiss Stereoplanigraph C8. In plotting the pass points by the radial line method Zeiss Radialsecator RSI was used. As to map projection, the Lambert Conformal Conic Projection with Two Standard Parallels at 68°0'S and 70°0'S was applied. Finally, two sheets of 1 : 250,000 maps, "PRINCE OLAV COAST" -from 67°40' to 69°0'S and from 40°30' to 45°0'E, and "LUTZOW-HOLM BAY" -from 68°30' to 70°30'S and from 37°0' to 40°30'E were printed in eight colors. departmental bulletin paper